2022
DOI: 10.1002/jso.26825
|View full text |Cite
|
Sign up to set email alerts
|

Breast and thyroid cancer: A multicenter study with Accrual to Clinical Trials Network

Abstract: Objective: To investigate a possible link between breast and thyroid cancer.Methods: A multicenter retrospective review of patients in the electronic medical records of six Accrual to Clinical Trial (ACT) institutions with both breast cancer and thyroid carcinoma. Each center queried its data using a predefined data dictionary. Information on thyroid and breast cancer included dates of diagnosis, histology, and patient demographics.Results: A random-effects model was used. There were 4.24 million women's recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Taking the IVW fixed effects model as an example, our MR OR value (1.9146, 95% CI: 1.0147–3.6127) undoubtedly coincides with this finding. In a multicenter study conducted this year, the presence or absence of BN was not linked to the presence or absence of TN ( 22 ). These observational research results are contradictory and are difficult to prove.…”
Section: Discussionmentioning
confidence: 99%
“…Taking the IVW fixed effects model as an example, our MR OR value (1.9146, 95% CI: 1.0147–3.6127) undoubtedly coincides with this finding. In a multicenter study conducted this year, the presence or absence of BN was not linked to the presence or absence of TN ( 22 ). These observational research results are contradictory and are difficult to prove.…”
Section: Discussionmentioning
confidence: 99%
“…These clinical studies assess the safety and effectiveness of new medications, combinations of treatments, and therapy modalities. Enrolling in clinical trials provides patients with access to novel treatments that may result in better outcomes ( 38 ). A comprehensive approach to therapy is ensured by the collaboration of endocrinologists, surgeons, radiation oncologists, and medical oncologists in customizing treatment programs depending on the diagnosis of each patient ( 38 ).…”
Section: Overview Of Thyroid Cancermentioning
confidence: 99%
“…Enrolling in clinical trials provides patients with access to novel treatments that may result in better outcomes ( 38 ). A comprehensive approach to therapy is ensured by the collaboration of endocrinologists, surgeons, radiation oncologists, and medical oncologists in customizing treatment programs depending on the diagnosis of each patient ( 38 ). Tracking therapy response and identifying any recurrence signals requires routine monitoring with imaging scans, blood tests, and clinical evaluations ( 38 ).…”
Section: Overview Of Thyroid Cancermentioning
confidence: 99%
“…However, the study was unable to fully exclude the possibility of a common etiology or the effects of treatment. In recent years, several studies have examined the risk of breast cancer in relation to thyroid cancer ( 17 19 ). The latest study on patients with differentiated thyroid cancer in children and young adults demonstrated a heightened risk of solid malignancies associated with radioactive iodine (RAI) treatment, with the risk of RAI-associated breast cancer being the most prominent after a 20-year follow-up ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latest study on patients with differentiated thyroid cancer in children and young adults demonstrated a heightened risk of solid malignancies associated with radioactive iodine (RAI) treatment, with the risk of RAI-associated breast cancer being the most prominent after a 20-year follow-up ( 18 ). Conversely, a comprehensive analysis of the medical records of 4.24 million women did not identify a correlation between breast cancer survivors and the risk of thyroid cancer ( 19 ). Similarly, an earlier analysis involving ten thyroid cancer registries worldwide, including 6,449 patients treated with radioiodine for differentiated thyroid carcinoma and 1,116 controls, failed to reveal a substantial increase in the risk of breast cancer following radioiodine treatment.…”
Section: Introductionmentioning
confidence: 99%